ROMANIAN IMPERATIVE FROM THE PERSPECTIVE OF PRAGMATIC PRINCIPLE OF (IM)POLITENESS - KELEMEN, Emilia (Studia Universitatis Babeș-Bolyai Philologia, 2020)
Romanian imperative from the perspective of pragmatic principle of (im)Politeness. Following a short presentation of the principle of politeness, the article approaches the Romanian imperative identifying negative and positive strategies of (im)politeness, which the imperative is part of. There were identified conventional forms of impoliteness of imperative. The exemplification of (im)polite strategies is based on a corpus elaborated by us. The imperative is present in the most diverse strategies of (im)politeness, however the occurrence of imperative does not mean the interlocutor’s threatening act toward the public image (face threatening act). The interpretation depends on several factors, among which the situation of the communication, the relationship between the interlocutors, the presence of intensifiers or attenuators etc. REZUMAT. Imperativul românesc din perspectiva principiului pragmatic al (im)politeții. După o scurtă prezentare a principiului politeții, articolul abordează imperativul românesc, identificând strategii ale (im)politeții negative și pozitive din care face parte imperativul. Au fost identificate formule convenționalizate de impolitețe cu imperativul. Exemplificarea strategiilor se face pe baza corpusului întocmit de noi. Imperativul ia parte la strategii ale (im)politeții dintre cele mai diverse, însă apariția imperativului nu înseamnă neapărat un act amenințător la adresa imaginii publice a interlocutorului. Interpretarea sa depinde de mai mulți factori, printre care situația de comunicare, relația dintre interlocutori, prezența intensificatorilor sau a atenuatorilor etc. Cuvinte cheie: imperativ, politețe, imagine individuală, strategii de politețe, impolitețe.